Words ‘svet’ [Light] and ‘solntse’ [Sun] as Main Representatives of Concept LIGHT in Work of M. M. Prishvin - G. N. Abreimova; M. V. Klimova; U. I. Turko (Научный диалог, 2022)
The features of the content structure of the concept LIGHT in the work of M. M. Prishvin is discussed in the article. The writer’s works and diaries covering the period from 1905 to 1954 are used as a source of material. A comprehensive analysis of the linguistic material has been carried out and some individual author’s interpretations of the implicit meaning of the concept LIGHT have been identified. The work was carried out within the framework of the AntCont program, in which a corpus of 83 documents representing the writer’s texts was formed. Particular attention is paid to the semantic components of the analyzed concept, which are revealed through the reconstruction of its nominative field, including various lexico-semantic groups. The statistical indicators of nouns associated with the concept of LIGHT made it possible to single out high-frequency, mid-frequency and low-frequency units that make up the core and periphery of the concept. A corpus analysis of lexical units representing the core of the concept LIGHT was carried out in combination with the methods of component, contextual and distributional analysis. With the help of the immediate environment, 7 main features of the nuclear components (‘svet’ [light] and ‘solntse’ [sun]) that make up the concept of LIGHT in the work of M. Prishvin were identified: temporality, location, intensity, color, spirituality, temperature, appraisal.